Phosphorus fluxes and recovery options in the wastewater system of the city of Luleå, Northern Sweden - Herrmann, Inga; Hedström, Annelie; Viklander, Maria (Luleå tekniska universitet, Arkitektur och vatten, 2012)
Phosphorus fluxes in Sweden’s municipal wastewater systems are barely known today and phosphorus recovery is poor in many systems. Further, there are about one million on-site treatment facilities, of which a majority has a low phosphorus capturing potential. There is a need to identify phosphorus losses and recovery options in the systems to increase phosphorus recovery both on centralised and decentralised level. This study focuses on the municipality of Luleå, northern Sweden. Luleå’s sanitary system is partly centralised (discharging to a WWTP with a moving bed biofilm reactor and chemical phosphorus precipitation) and partly decentralised (with several small-scale or on-site treatment facilities). The aim of this study is to identify and quantify phosphorus fluxes, including phosphorus recovery rates and losses, in the municipality’s existing sanitary system. Furthermore, alternative and innovative sanitary systems are analysed towards their phosphorus fluxes and recovery options. The study therefore contributes to more sustainable sanitation systems Godkänd; 2012; 20121126 (ingher)